Direct binding of polymeric GBP1 to LPS disrupts bacterial cell envelope functions. (8th June 2020) - Kutsch, Miriam; Sistemich, Linda; Lesser, Cammie F; Goldberg, Marcia B; Herrmann, Christian; Coers, Jörn
Abstract: In the outer membrane of gram‐negative bacteria, O‐antigen segments of lipopolysaccharide (LPS) form a chemomechanical barrier, whereas lipid A moieties anchor LPS molecules. Upon infection, human guanylate binding protein‐1 (hGBP1) colocalizes with intracellular gram‐negative bacterial pathogens, facilitates bacterial killing, promotes activation of the lipid A sensor caspase‐4, and blocks actin‐driven dissemination of the enteric pathogen Shigella . The underlying molecular mechanism for hGBP1's diverse antimicrobial functions is unknown. Here, we demonstrate that hGBP1 binds directly to LPS and induces "detergent‐like" LPS clustering through protein polymerization. Binding of polymerizing hGBP1 to the bacterial surface disrupts the O‐antigen barrier, thereby unmasking lipid A, eliciting caspase‐4 recruitment, enhancing antibacterial activity of polymyxin B, and blocking the function of the Shigella outer membrane actin motility factor IcsA. These findings characterize hGBP1 as an LPS‐binding surfactant that destabilizes the rigidity of the outer membrane to exert pleiotropic effects on the functionality of gram‐negative bacterial cell envelopes. Synopsis: Human Guanylate Binding Protein 1 (hGBP1) provides intracellular host defense to gram‐negative bacteria expressing lipopolysaccharide (LPS) on their surfaces. Using novel in vitro binding assays as well as cell biological approaches this study reveals that hGBP1 operates as an LPS‐binding and ‐clustering surfactant to destabilize the gram‐negative outer membrane, thereby rendering hGBP1‐bound bacteria susceptible to attacks by other antimicrobial molecules. Polymerizing hGBP1 binds directly to LPS and to gram‐negative bacteria. A stable hGBP1 protein coat is formed on bacteria expressing O‐antigen. hGBP1 clusters LPS molecules and disrupts the O‐antigen barrier function. hGBP1 disturbs O‐antigen‐dependent function of the Shigella virulence protein IcsA. Abstract : Human Guanylate Binding Protein 1 (hGBP1) binds to LPS to destabilize gram‐negative outer membranes and thereby promoting antibacterial host defense pathways.